2009
DOI: 10.4103/0022-3859.57393
|View full text |Cite
|
Sign up to set email alerts
|

Inducible clindamycin resistance in Staphylococcus aureus

Abstract: Clindamycin is kept as a reserve drug and is usually advocated in severe MRSA infections depending upon the antimicrobial susceptibility results. We have reported a higher incidence of iMLS(B) from both community (66.67%) as well as hospital (33.33%) setup. Therefore clinical microbiology laboratory should report inducible clindamycin resistance routinely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
44
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 9 publications
12
44
2
Order By: Relevance
“…In the present study, 15.53% of the MSSA isolates showed iMLSB resistance, which correlates with the findings by Delialiogu et al, who reported 10.7% iMLSB resistance in the MSSA isolates and Gupta at al who reported 17.3% iMLSB resistance in the MSSA isolates [3] [12].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, 15.53% of the MSSA isolates showed iMLSB resistance, which correlates with the findings by Delialiogu et al, who reported 10.7% iMLSB resistance in the MSSA isolates and Gupta at al who reported 17.3% iMLSB resistance in the MSSA isolates [3] [12].…”
Section: Discussionsupporting
confidence: 81%
“…Angel et al have not found any cMLSB resistance in the S.aureus strains. However, Gupta et al have reported 19% cMLB resistance, 46% of which were of the MRSA type and 10% were of the MSSA type [10] [12]. 15.65% S.aureus strains showed the MSB phenotype in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Clindamycin, the macrolide-lincosamide-streptogramin B (MLSB) antimicrobial group is an alternative treatment option for S. aureus infections 9,8 . The use of this antimicrobial agent in the presence of erythromycin resistance is of a great concern, since there is a possibility of induction of cross-resistance mechanism among members of the MLSB 10 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in accordance with Date et al, (2012) who found 26.43% of total isolates showed constitutive resistance, which was more frequent in MRSA 52.63% and MR-CoNS 78.95% and Shantala et al, (2011) who found a higher incidence of cMLSB in S. aureus 18.26% (19,20) . Gupta et al, (2009); have reported cMLSB resistance in 19% of total isolates of which 46%were MRSA type and ten%were MSSA type (21) . In this study, higher incidence of cMLSB resistance was found in CoNS 41.57%.…”
Section: Discussionmentioning
confidence: 99%